The Effect of Modified Banana Flour and Soy Flour Ratio on The Organoleptic Parameters of Snack Bar as Supplementary Food in Type 2 Diabetes Mellitus Patients - Firdaus Syafii; Ahmad Yani (Journal of Noncommunicable Diseases Prevention and Control, 2023)
This study aims to determine the effect of modified banana flour and soybean flour formulations on the organoleptic properties of snack bars. The formulation used in this study was based on the ratio of differences in the use of modified kepok banana flour with soy flour. The design used in this study was a complete randomized design (RAL). The factors used in this study were 5 formulations with a ratio of modified kepok banana flour and soybean flour, namely F1 (100:0), F2 (70:30), F3 (50:50), F4 (30:70), and F5 (0:100). The response measured in this design is a hedonic test (favorability level), which includes taste, aroma, color, and texture attributes. The selected snack bar formula results from the hedonic test are then tested for water content, protein content, and fiber content. Based on the results of hedonic test analysis on 5 formulas using the ANOVA test, it showed significant results (p<0.05) for the hedonic test response of taste, aroma, and texture attributes and an insignificant response (p>0.05) to the hedonic test of color attributes. Formula F3 with a modified ratio of banana flour and soy flour (50:50) is the most preferred formula based on taste attributes (4.48), aroma (4.40), and texture (4.37). A snack bar with formula F3 has a moisture content of 4.58%, a protein content of 18.28%, and a fiber content of 13.42%. The high protein and fiber content in this snack bar makes it suitable as a supplementary food for consumption by people with type 2 diabetes mellitus.